2023
DOI: 10.1021/acsaom.2c00180
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced and Broadened NIR Emission of CaZnGe2O6:Cr3+ by Yb3+ Codoping for NIR Applications

Abstract: Compact and portable near-infrared (NIR) light sources have been widely used in the fields of NIR spectroscopy, night vision lighting, medical measurement, etc. Although Cr 3+ -activated phosphors have been widely reported, achieving broadband and high-efficiency near-infrared emission remains of great significance. In this work, CaZnGe 2 O 6 :Cr 3+ with highly efficient and ultrabroadband NIR emission was synthesized by a solid reaction method, and Yb 3+ -codoping not only enhanced the NIR emission efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The energy barrier between the lowest excited state 4 T 2 and the conduction band can be empirically determined using the equation, . Δ E P for SLLT:3%Cr 3+ is 0.52 K. Thermal activation energies of the phosphors above room temperature were calculated using the Arrhenius equation given by 23,24,29 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The energy barrier between the lowest excited state 4 T 2 and the conduction band can be empirically determined using the equation, . Δ E P for SLLT:3%Cr 3+ is 0.52 K. Thermal activation energies of the phosphors above room temperature were calculated using the Arrhenius equation given by 23,24,29 …”
Section: Resultsmentioning
confidence: 99%
“…2 F 5/2 → 2 F 7/2 emission transitions of Yb 3+ serve as an effective means to circumvent nonradiative transitions between different energy levels, consequently enhancing the thermal stability of the phosphors. [22][23][24][25][26][27][28][29] Cr 3+ and Yb 3+ co-doped NIR phosphors have been recently studied as spectral converters for solar cell applications since Yb 3+ emission matches well with the spectral response of Sisolar cells. 30 Inspired by this, the combination of Cr 3+ and Yb 3+ has been utilized by many researchers to develop NIR pc-LEDs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One such material is CaZnGe 2 O 6 [calcium zinc germanate (CZGO)], which is a clinopyroxene material utilized in long persistent luminescence phosphors. 33−36 The dopants used in CZGO clinopyroxene include chromium (Cr); 35,37 manganese (Mn); 33,38 bismuth (Bi); 33,39 dysprosium (Dy); 36 terbium (Tb), 34 and lead (Pb). 17 In particular, Dong et al recently reported the synthesis and application of leaddoped CZGO (CZGO: Pb) with dynamic fluorescence and photochromic properties.…”
Section: ■ Introductionmentioning
confidence: 99%